Today's reforms of tax administration in our country - Mukimov Botir Mirabzalovich (Genius Journals, 2023)
This article examines the problems and opportunities in the tax administration of Uzbekistan and suggests practical ways to increase its efficiency. The tax system plays an important role in revenue generation and economic development. However, some inefficiencies and complexities within the administration prevent optimal tax collection and enforcement. The review of the current tax administration in Uzbekistan begins with showing its strengths and weaknesses. Suggested ways to improve tax administration in Uzbekistan include implementing digital solutions, simplifying tax procedures, and adopting a risk-based approach to auditing. The study provides practical recommendations to help create a stronger tax system and a more favorable business environment in the country.
Keywords: Tax administration methodology; tax administration land; land tax